Behavioural measures determine survivorship within the hierarchy of whole‐organism phenotypic traits. (15th January 2018) - McCormick, Mark I.; Fakan, Eric; Allan, Bridie J. M.
Abstract: Mortality through predation is often selective, particularly at life‐history bottlenecks. While many studies have looked at the importance for survival of specific prey characteristics in isolation, few have looked at a broad array of attributes and how they relate to survival in a realistic context. Our study measures 18 morphological, performance and behavioural traits of a juvenile damselfish that have been hypothesized as important for prey survival, and examines how they relate to survival in the field immediately after settlement. These attributes included size, relative false eye‐spot size, fast‐start escape response kinematics, thigmotaxis, laterality, and space use and activity in the field. Using conditional inference trees, we identify the most important drivers out of a reduced suite of 13 characters. Fast‐start response latency, boldness, feeding rates and two measures of activity were found to significantly contribute to survival. Morphological variables and most laboratory measures of performance appeared to contribute little to survival. Results suggest selection works on a suite of characters associated with boldness. Bold and active fish are those that will be best able to learn using public information, but because of the relative naiveté of newly metamorphosed fishes, speed to react to a strike from an unknown predator is of critical importance. Findings substantiate the ecomorphological paradigm by suggesting that selection on behaviour modifies the correlations of morphological and performance variables with survival probabilities, since behaviour modifies performance capabilities by making them specific to context. A plain language summary is available for this article. Abstract : Plain Language Summary